2016
DOI: 10.1016/j.biortech.2016.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-based pretreatments distinctively extract lignin and pectin for enhancing biomass saccharification by altering cellulose features in sugar-rich Jerusalem artichoke stem

Abstract: Jerusalem artichoke (JA) has been known as a potential nonfood feedstock for biofuels. Based on systems analysis of total 59 accessions, both soluble sugar and ash could positively affect biomass digestibility after dilute sodium hydroxide pretreatment (A). In this study, one representative accession (HEN-3) was used to illustrate its enzymatic digestibility with pretreatments of ultrasonic-assisted dilute sodium hydroxide (B), alkaline peroxide (C), and ultrasonic-assisted alkaline peroxide (D). Pretreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 31 publications
4
45
0
Order By: Relevance
“…Li et al . used four different alkali-based pretreatments to pretreat stems of Jerusalem artichoke and found that alkali pretreatment as the most effective technique in removing non-cellulosic polymers 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Li et al . used four different alkali-based pretreatments to pretreat stems of Jerusalem artichoke and found that alkali pretreatment as the most effective technique in removing non-cellulosic polymers 23 .…”
Section: Introductionmentioning
confidence: 99%
“…All sorghum samples were harvested on their dates of physiological maturity after a growth period of between 110 and 150 days. Preparation of samples was performed according to the process described by Li et al [ 3 ] with minor modifications. In this study, stem samples were ground using a crusher mill into particles 1–2 cm in size.…”
Section: Methodsmentioning
confidence: 99%
“…The soluble sugar was extracted with distilled water and determined by the anthrone/H 2 SO 4 method using a UV–VIS spectrometer (TU-1901, Beijing Purkinje Instruments Co. Ltd., Beijing, China) according to Li et al [ 3 ] The standard curve was plotted using d -glucose as the standard (purchased from Xilong Scientific Co., Ltd., China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignocellulosic biomass is a plentiful, sustainable, and non-food resource that can be used to produce alternative fuels and valuable chemicals to address the concerns of increasing energy consumption and environmental pollution (Himmel et al, 2007;Li et al, 2016). However, the processing of lignocellulosic biomass is much more challenging than bioconversion of corn starch or sugarcane to liquid fuels, due to the inherent recalcitrance of lignocelluloses to enzymatic or microbial decomposition.…”
Section: Introductionmentioning
confidence: 99%